1994
DOI: 10.1007/bf01347702
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of powdered pine bark for control ofMeloidogyne arenaria andHeterodera glycines on soybean

Abstract: Commercially available pine bark nuggets (composted) and fresh pine bark were ground into powders and added at rates of 0 to 50 g kg-l to field soil infested with Meloidogyne arenaria and Heterodera glycines. The treated soil was maintained moist in the greenhouse for 2 weeks, sampled, and planted with 'Davis' soybean (Glycine max.). Eight weeks after planting, numbers of M. arenaria and H. glycines in soil decreased with increasing amounts of composted or fresh pine bark. No juveniles were present in soil tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 8 publications
1
8
0
1
Order By: Relevance
“…Additionally, the incorporation of crop residues favours cellulolytic microorganisms compared with those that cannot degrade cellulose (Debosz et al, 1999). The increase in microbial biomass, as indicated by an increase in esterase activity, was due to the addition of OM, as no such increase was found in the unamended control treatment (Kokalis-Burelle et al 1994). Similar results were reported when untreated OM or compost were applied to soil (Kandeler et al, 1999;Pérez-Piqueres et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Additionally, the incorporation of crop residues favours cellulolytic microorganisms compared with those that cannot degrade cellulose (Debosz et al, 1999). The increase in microbial biomass, as indicated by an increase in esterase activity, was due to the addition of OM, as no such increase was found in the unamended control treatment (Kokalis-Burelle et al 1994). Similar results were reported when untreated OM or compost were applied to soil (Kandeler et al, 1999;Pérez-Piqueres et al, 2006).…”
Section: Discussionsupporting
confidence: 62%
“…as Kokalis-Burelle et al (1994) found that invertase activity doubled in soil amended with pine bark compared with soil amended with composted bark.…”
Section: Discussionmentioning
confidence: 92%
“…Soil samples (100 g each) were collected from all replications at each sampling time, dried, stored, and analyzed for pH and electrical conductivity as described by Kokalis-Burelle et al (1994).…”
Section: Soil Analysis and Storagementioning
confidence: 99%
“…3.2.1.26) activity was determined using a modification of Hofmann's procedure (Hofmann, 1963) described by Kokalis-Burelle et al (1994). Invertase (beta-fructofuranoside fructohydrolase, E.C.…”
Section: Enzyme Analysismentioning
confidence: 99%
“…They (including juveniles and soils) were absolutely absent up till 70% dust addition treatments. The inhibitory effect of sawdust on nematodes can be attributed to the formation of phenolic compounds by the decomposition of sawdust (Kokalis-Burelle et al, 1994). For juveniles and galling, the concentration of some formed phenollic compounds of about 30% dust amendments could not have crossed the threshold limit so as Table 9.…”
Section: Discussionmentioning
confidence: 99%